2001
DOI: 10.1097/00002371-200105000-00012
|View full text |Cite
|
Sign up to set email alerts
|

CD20-Directed Antibody-Mediated Immunotherapy Induces Responses and Facilitates Hematologic Recovery in Patients With Waldenstrom’s Macroglobulinemia

Abstract: Waldenstrom's macroglobulinemia (WM, lymphoplasmacytic lymphoma) is a B-cell lymphoproliferative disorder in which CD20 is expressed on tumor cells from most patients. Several small studies have suggested a benefit from the anti-CD20 monoclonal antibody rituximab (Rituxan, MabThera) in patients with WM. In this retrospective study, we examined the outcome of 30 previously unreported patients with WM who received treatment with single-agent rituximab (median age 60; range 32-83 years old). The median number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(55 citation statements)
references
References 14 publications
0
55
0
Order By: Relevance
“…[38][39][40] In patients with both treatment-naïve and previously treated Waldenström macroglobulinemia, rituximab has been associated with response rates ranging from 29% to 65%. [40][41][42][43][44] Over time, it has become clear that the best response to rituximab may not be seen for many months after treatment. 43 This may result in an underestimation of the activity of rituximab considering that the response end points in most clinical trials are at earlier time points.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…[38][39][40] In patients with both treatment-naïve and previously treated Waldenström macroglobulinemia, rituximab has been associated with response rates ranging from 29% to 65%. [40][41][42][43][44] Over time, it has become clear that the best response to rituximab may not be seen for many months after treatment. 43 This may result in an underestimation of the activity of rituximab considering that the response end points in most clinical trials are at earlier time points.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…54,62 The use of rituximab is best avoided as single-agent therapy in patients with high IgM levels because in 2 studies considerably lower response rates were observed in those patients with higher serum IgM levels (Ͼ 4000 mg/dL). 64,65 …”
Section: Treatment Of the Wm Patient Requiring Immediate Disease Controlmentioning
confidence: 99%
“…The use of rituximab as a single agent can also be considered in select patients with WM, such as those presenting with a low tumor burden, mild to moderate cytopenias resulting from bone marrow involvement or autoimmune-related destruction (ie, cold agglutinemia, immune mediated thrombocytopenia), or IgM-related neuropathy (see "Treatment of peripheral neuropathy"). Overall response rates with 4 weekly infusions of rituximab are 20% to 30%, [64][65][66] whereas the use of extended-dose rituximab (ie, 4 weekly infusions followed by 4 more weekly infusions at week 12) has been associated with higher overall response rates (40%-50%). 67,68 Polymorphisms in position 158 of the CD16 (Fc␥RIIIA-158) receptor have been shown in WM and related indolent lymphomas to predict response.…”
Section: Treatment Of the Wm Patient Requiring Nonimmediate Disease Cmentioning
confidence: 99%
“…Similarly, patients treated initially with rituximab who experience relapse after 6 months or more should be treated with rituximab, alkylating agents, or nucleoside analogs; these patients who experience progressive disease or early relapse should be treated with alkylating agents or nucleoside analogs. Patients whose disease progresses after second-line therapy are candidates for salvage therapies (e.g., hematopoietic SCT; monoclonal antibodies such as rituximab; 131 thalidomide with or without dexamethasone) in the context of clinical trials. Ongoing trials are evaluating lenalidomide and bortezomib, alone and in combination, for treating Waldenström's macroglobulinemia.…”
Section: Follow-up and Surveillancementioning
confidence: 99%